Training Entrepreneurship For Sustainable Rehab Program Participants For Development Clients Who Receive Monitoring And Assistance From The National Narcotics Agency (Bnn) West Java Province (Business example: Dorokdokcu Business) - et. al., Yelli Eka Sumadhinata, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
West Java Province is one of the highest areas in the abuse and trafficking of narcotics. Especially during the pandemic, the rate of narcotics abuse cases actually increased twofold. Therefore, various strategic steps were taken by the West Java BNNP for thefor Programthe Prevention, Eradication of Drug Abuse and Illicit Drug Trafficking (P4GN). BNN expects a synergistic relationship between related institutions by always supporting the P4GN programs launched by BNN. As one of the steps of concern for the Educational Institution in participating actively in the government program, as an effort to save rehabilitated drug users from returning to the community, Widyatama University, through the Community Service program through Clusters, collaborates with BNN to provide training. Entrepreneurship for assisted clients who receive monitoring and assistance from the National Narcotics Agency (BNN) of West Java Province. Entrepreneurship training is provided with the aim of providing provision in terms of increasing the ability and willingness of BNN-assisted clients to be more ready to go back into the community. This extension activity was held in collaboration with Widyatama University and the National Narcotics Agency of West Java Province, where this training was held on 15-20 February 2021. There are 80 outreach participants. The results obtained from this Community Service Activity are where the participants have motivation and are able to practice and develop what they get during the training, namely starting a business